2013
DOI: 10.1002/pip.2360
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Mo back contact ageing on Cu(In,Ga)Se2 thin‐film solar cells

Abstract: In this work, we investigate the effect of ageing Mo-coated substrates in a dry and N 2 flooded cabinet. The influence was studied by preparing Cu(In,Ga)Se 2 solar cells and by comparing the electrical performance with devices where the Mo layer was not aged. The measurements used for this study were current-voltage (J-V), external quantum efficiency (EQE), secondary ion mass spectroscopy (SIMS) and capacitance-voltage (C-V). It was concluded that devices prepared with the aged Mo layer have, in average, an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…It has been theoretically proposed [91] and experimentally verified [92] that the mechanism responsible for Na diffusion is a H þ /Na þ ion exchange process and that the H þ is being stored in the Mo layer during air exposure whereas the source of Na is Na 2 O present in the glass [93]. The diffusion of Na from the SLG through the Mo proceeds via oxygenated Mo grain boundaries [92,94] and it has also been shown that oxygenated Mo layers provide CIGSe with higher Na concentrations [57,95]. It is worth mentioning that the amount of Na that diffuses is of Table 2 Typical composition of SLG (only the main constituents are given) [88].…”
Section: Soda-lime Glassmentioning
confidence: 95%
“…It has been theoretically proposed [91] and experimentally verified [92] that the mechanism responsible for Na diffusion is a H þ /Na þ ion exchange process and that the H þ is being stored in the Mo layer during air exposure whereas the source of Na is Na 2 O present in the glass [93]. The diffusion of Na from the SLG through the Mo proceeds via oxygenated Mo grain boundaries [92,94] and it has also been shown that oxygenated Mo layers provide CIGSe with higher Na concentrations [57,95]. It is worth mentioning that the amount of Na that diffuses is of Table 2 Typical composition of SLG (only the main constituents are given) [88].…”
Section: Soda-lime Glassmentioning
confidence: 95%
“…[50] The reference device has a median CIGS (apparent) doping concentration at 0 V of 3.2 × 10 16 cm −3 with a standard deviation of 0.3 × 10 16 cm −3 , whereas the passivated devices present an average of 1.9 × 10 16 cm −3 with a standard deviation of 0.3 × 10 16 cm −3 . [50] The reference device has a median CIGS (apparent) doping concentration at 0 V of 3.2 × 10 16 cm −3 with a standard deviation of 0.3 × 10 16 cm −3 , whereas the passivated devices present an average of 1.9 × 10 16 cm −3 with a standard deviation of 0.3 × 10 16 cm −3 .…”
Section: Wwwadvmatinterfacesdementioning
confidence: 99%
“…Another interesting aspect related to the Mo back contact is its oxygen content; it has been reported for both CIGS and CZTSSe a beneficial effect for solar cell performance when present in a certain amount [29,30]. In the case of CZTS, an increase in O content in the Mo back contact, via annealing in N 2 atmosphere at 550ºC for 10 min, coupled with an increase in Na content, led to a reduction of the MoS 2 layer after the thermal annealing, reducing considerably the R S [30].…”
Section: Introductionmentioning
confidence: 99%